2010
DOI: 10.3382/ps.2010-00749
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-gallate prevents lipid peroxidation and enhances antioxidant defense system via modulating hepatic nuclear transcription factors in heat-stressed quails

Abstract: Epigallocatechin-3-gallate (EGCG), a polyphenol derived from green tea, exerts antioxidant effects. Oxidative stress is one of the consequences of heat stress (HS), which also depresses performance in poultry. This experiment was conducted to elucidate the action mode of EGCG in alleviation of oxidative stress in heat-stressed quail (Coturnix coturnix japonica). A total of 180 five-week-old female Japanese quails were reared either at 22°C for 24 h/d (thermoneutral, TN) or 34°C for 8 h/d (HS) for 12 wk. Birds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
85
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(91 citation statements)
references
References 52 publications
5
85
0
1
Order By: Relevance
“…Very few studies have been conducted on poultry, and they produced inconsistent results regarding the direction and range of the antioxidant effects of polyphenols in birds. Jiang et al (2007) reported that dietary isoflavones from soybean increase SOD activity and decreased plasma TBARS levels in broiler chickens, whereas other authors demonstrated that dietary supplementation with purified flavonoids increased only blood vitamin E concentrations in Japanese quails (Sahin et al 2010). In another experiment, an increase in GSH-Px activity and a tendency towards higher levels of SOD activity were not accompanied by changes in the FRAP or TBARS values in the blood of broilers (Vossen et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Very few studies have been conducted on poultry, and they produced inconsistent results regarding the direction and range of the antioxidant effects of polyphenols in birds. Jiang et al (2007) reported that dietary isoflavones from soybean increase SOD activity and decreased plasma TBARS levels in broiler chickens, whereas other authors demonstrated that dietary supplementation with purified flavonoids increased only blood vitamin E concentrations in Japanese quails (Sahin et al 2010). In another experiment, an increase in GSH-Px activity and a tendency towards higher levels of SOD activity were not accompanied by changes in the FRAP or TBARS values in the blood of broilers (Vossen et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Jiang et al (2007) reported a dose-dependent increase in plasma total antioxidant activity of broilers whose diets were supplemented with 10 to 80 mg/kg of soy flavonoids. An improvement in plasma antioxidant parameters, including total antioxidant activity and MDA concentrations, was reported when broiler diets were supplemented with grape-derived resveratrol (Sahin et al 2010), rosemary, green tea and grape seed extracts (Vossen et al 2011), and purified genistein and hesperidin (Kamboh and Zhu 2013). Similar results were noted in our study where the addition of fruit pomaces, in particular seedless strawberry pomace, improved selected parameters of antioxidant status in the blood plasma, including an increase in vitamin C levels, catalase activity, capacity of hydrophilic and lipophilic fractions, and FRAP values, and a decrease in plasma peroxide levels and TBARS values in turkey livers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Current studies informed that green tea catechins, the main components of green tea leaf, have many physiological and biochemical functions, including antioxidant (radical and oxidant scavenging, metal chelating, and inhibition of pro-oxidant enzymes), antimicrobial, anticarcinogenic, hypoallergic and blood glucose reduction in studies on different animal species (Frei & Higdon 2003;Koo & Cho 2004;Zhong et al 2009;Ariana et al 2011;Kara & Guclu 2012). The studies carried out on hens and quail emphasized especially the antioxidation effect on the blood and the animal products (meat and egg) and also on performance (Tang et al 2000;Biswas et al 2000;Abdo et al 2010;Sahin et al 2010;Ariana et al 2011). The change in performance parameters such as live weight, feed intake, egg production, and feed efficiency was not observed in some studies which used green tea leaves or extracts (Biswas et al 2000;Biswas & Wakita 2001;Ariana et al 2011) as corresponding with results of the present study, and despite that in some studies these parameters had a negative effect (Uuganbayar et al 2006;Kojima & Yosida 2008;Sarker et al 2010).…”
Section: Discussionmentioning
confidence: 99%